The Post-mortem Examination in Ruminants and its Possible Benefit to Ruminant Clinical Medicine. Issue 2 (February 2017) - Wäsle, K.; Pospischil, A.; Hässig, M.; Gerspach, C.; Hilbe, M.
Summary: To highlight the important role of post-mortem examination of ruminants and to identify possible benefits for modern ruminant medicine, a comparison of clinical and pathological diagnoses was conducted and influencing factors were identified. For this purpose, results from 2, 000 ruminants that had undergone necropsy examination at the University of Zurich, Switzerland, were analysed retrospectively. Both clinical and pathological diagnoses were available for 81.40% of cattle, 80.22% of sheep and 66.66% of goats; no diagnoses were available for 3.86% of cattle, 3.30% of sheep and 7.41% of goats. In the remaining cases, either the pathological diagnosis or the clinical diagnosis was unavailable. The greatest influences on the presence of diagnoses were the way in which the animal died, the type of necropsy examination and the age of the animal. The majority of diagnoses were attributed to digestive and respiratory disorders in cattle and digestive, neurological and urinary disorders in small ruminants. The main clinical diagnoses was confirmed pathologically in 86.20% of cattle, 85.51% of sheep and 82.00% of goats, while 7.03% of diagnoses in cattle, 12.26% in sheep and 11.00% in goats could not be confirmed by post-mortem or histopathological examinations. Relevant additional information or specification of diagnoses was given in 70.87% of cattle, 45.21% of sheep and 56.66% of goats. The concurrence of diagnoses and diagnosis specification was most influenced by the way in which the animal died, the type of necropsy examination that was conducted, the performance of histopathology following the necropsy examination and whether the animal was submitted in connection with a livestock health problem. This study highlighted the abiding importance of the post-mortem examination in modern ruminant medicine, despite technical advances in clinical technologies, both as a diagnostic tool and for quality control.